Accounting Transformation Challenges and Opportunities in The Ongoing Twenty-First Century: A Study in Nepal - Niroula, Arjun Kumar; Pant, Ganesh Datt (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study aims to analyze the evolution of accounting practices in the digital era, focusing on the transformation challenges and opportunities in the ongoing twenty-first century in a Nepalese context. The office secretarial theories applicable to the association between new digital technology and major accounting concepts and practices, such as agency theory, stakeholder theory, legitimacy theory, and technology theory. This study employed a narrative review methodology that synthesizes several literatures to thoroughly examine the function of accounting transparency theories in the digital age. The result shows that although technologies like artificial intelligence improve the accuracy and efficiency of accounting procedures, they also carriage difficulties because of the speed at which technology is developing, which is faster than traditional accounting practices. Specifically, new technologies complicate monitoring automated systems, require stakeholder management upgrades, challenge the current accountabilities framework to test, and make financial data interpretation more difficult. Practical applications are lacking as a result of conventional accounting practices' inability to keep records up. The study to ensure that accounting not only keeps up with technical advancement but also upholds a high standard of accountability, credibility, and transparency. The research study emphasizes the need for new accounting theories that may bridge the gap between cutting-edge technological capabilities and present practice for challenges and opportunities in the accounting field.